2016
DOI: 10.3310/hta20160
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Now to Eliminate Repeat Unintended Pregnancy in Teenagers (INTERUPT): a systematic review of intervention effectiveness and cost-effectiveness, and qualitative and realist synthesis of implementation factors and user engagement

Abstract: BackgroundThe UK has one of the highest rates of teenage pregnancies in Western Europe. One-fifth of these are repeat pregnancies. Unintended conceptions can cause substantial emotional, psychological and educational harm to teenagers, often with enduring implications for life chances. Babies of teenage mothers have increased mortality and are at a significantly increased risk of poverty, educational underachievement and unemployment later in life, with associated costs to society. It is important to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 143 publications
6
36
0
Order By: Relevance
“…Qualitative and prospective research is needed to move towards the design of regional or country‐level public health strategies aimed at supporting adolescents in planning their lives, including educational and occupational opportunities, and having children when they desire them (as well as the number of children desired). In addition, implementation studies and other programme evaluations are needed to explain and resolve problems with existing services, as well as to understand issues in intervention design, implementation, and scaling‐up . Finally, as with all reproductive health issues, when considering pregnancy desire, gender inequalities should be taken into account…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative and prospective research is needed to move towards the design of regional or country‐level public health strategies aimed at supporting adolescents in planning their lives, including educational and occupational opportunities, and having children when they desire them (as well as the number of children desired). In addition, implementation studies and other programme evaluations are needed to explain and resolve problems with existing services, as well as to understand issues in intervention design, implementation, and scaling‐up . Finally, as with all reproductive health issues, when considering pregnancy desire, gender inequalities should be taken into account…”
Section: Discussionmentioning
confidence: 99%
“…Compared with adolescent mothers with only one child, young mothers with more than one child have lower levels of education, are more likely to live in poverty, and have increased dependence on governmental support (Rotermann 2007;Patchen et al 2013;Gill et al 2016). Lack of postpartum contraception (Al-Sahab et al 2012;Kingston et al 2012;Pinzon and Jones 2012;Wilson et al 2013;Whitaker et al 2016;Sober et al 2017), experiencing intimate partner violence (IPV), and having mental health and substance abuse issues (Harrison et al 2014;SmithBattle and Freed 2016) have been identified as key factors associated with multiple pregnancies among youth.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, our findings did not imply an association between use of dicloxacillin and the risk of oral contraceptive failure. However, oral contraceptive failure may have severe social consequences [25,26]. Acknowledging the limited statistical power and the potential downward biases present in our study, as well as the increased risks seen specifically for progestogen-only oral contraceptives, we therefore suggest supplementary physical barrier methods be used until 2 weeks after discontinuation of dicloxacillin, at least until further studies confirm the lack of an association.…”
Section: Discussionmentioning
confidence: 81%
“…The study population comprised 364 women with a median age of 23 [interquartile range (IQR) [19][20][21][22][23][24][25][26][27][28][29]. Of these, 40…”
Section: Resultsmentioning
confidence: 99%